Antiviral activity of Humulus lupulus (HOP) aqueous extract against MERS-CoV and SARS-CoV-2: in-vitro and in-silico study - Thamer Ahmed Bouback; Amal Mohammed Aljohani; Abdulaziz Albeshri; Hasan Al-Talhi; Yassmin Moatasim; Mohamed GabAllah; Raied Badierah; Raed Albiheyri; Faisal Al-Sarraj; Mohamed Ahmed Ali (Biotechnology & Biotechnological Equipment)
Coronaviruses emerged three times in the last two decades and became a source of concern globally. Humulus lupulus plant has been used widely in medical science. Our objective in this study was to determine the effects of the crude extract of H. lupulus in inhibiting MERS-CoV and SARS-CoV-2 viruses’ replication in vitro using Vero E6 cell lines and predict the antiviral activity of its identified compounds against the receptor binding (RBD) protein of both viruses in silico. We determined the concentration of the extract that induced less than 50% cell toxicity (CC50), and the antiviral activity based on IC50 and plaque reduction assay. We used molecular docking simulation to predict the potential of known active compounds in H. lupulus to inhibit the RBD protein. H. lupulus extract showed very low toxicity on Vero E6 cells with CC50= 23.25 µg/µL and antiviral activity toward MERS-CoV and SARS-CoV-2 with IC50= 0.18 and 0.9 µg/µL, respectively. The crude extract showed inhibition rate of 84.6% with MERS-CoV and 80% with SARS-CoV-2. In silico analysis predicted the compounds 5′-prenylxanthohumo, xanthogalenol, dehydrocycloxanthohumol hydrate, 6-prenylnaringenin, isoxanthohumol, catechin gallate, epicatechin gallate, 8-prenylnaringenin and xanthohumol to inhibit MERS-CoV and SARS-CoV-2 invasion of host cells by interfering with viral spike protein and the host cell receptor recognition process. Drug likeness and toxicity risk prediction analysis confirmed their capability as potential drugs. Based on our findings, isolation, purification and testing of the suggested active compounds could lead to novel anti-coronavirus drugs.